(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
The article demonstrates with colonial and imperial cartographic references the evolution of the cartographic representation of the region between the Rivers Grande and Paranaíba before the consolidation of the Araxá’s territory with the creation of it’s county. As well, based on official information about Araxa’s administrative forming and of the regional counties forming, this article confirms the rise in the territory of the Araxá’s county, by the year of 1835, of all the counties that now are the Mesoregion of the Triangulo Mineiro and Alto Paranaíba (66 counties), as well as parts of the mesoregion of the Northwest Minas Gerais (5 counties) and the Central Mineira mesoregion (5 counties), totaling 76 counties. Therefore 8.9% of the counties of the Brazilian state of Minas Gerais come from the territory of Araxá.